Prospective Teacher as Environmental Agent: Between Hope, Opportunities and Possibilities Toward Sustainable Environmental - Ganes Gunansyah; Suryanti Suryanti; Durrotun Nafisah (FKIP Universitas Lampung, 2024)
Prospective Teacher as Environmental Agent: Between Hope, Opportunities and Possibilities Toward Sustainable Environmental. Objectives: This study aims to capture how students, as prospective teachers and environmental agents, voice hopes, opportunities, and possibilities in addressing socio-ecological and ecological problems of sustainable development. Method: Data was collected through questionnaires using Google form electronic format, interviews, and student activities during lectures. Findings: The research results show that students' understanding of environmental issues as a young generation is still dominated by disaster discourse and solution discourse, which emphasizes individual solutions, technological solutions, and anthropocentric views. It is known that students still consider waste and flooding to be the main problems. Meanwhile, regarding opportunities and possibilities, students see the need for active participation and full involvement in environmental actions such as campaigns through various media platforms, deliberations, sustainable environmental movements, and collective awareness as citizens and citizens of the world for the common good. Conclusion: By placing the environment as an essential and urgent problem, various risks can be prepared, anticipated, thought through, handled, minimized, and solutions sought to avoid social-ecological disasters in the future. Even though students' views are still within a limited range of lenses and dimensions, this has implications for the need for critical environmental learning in improving the quality of sustainable environmental education. Keywords: sustainable education, social ecology, hope, opportunity, possibility, environmental agent.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202465